Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD)Terhadap Motivasi Belajar dan Kemampuan Pemahaman Konsep Matematika - Nova Novita; Tasnim Rahmat; M. Imamuddin; Pipit Firmanti (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This research is based on the background of the problems found in grade IX of SMP N 1 Gunuang Omeh District that the low motivation of students in learning mathematics, this is characterized by students who look lazy in learning and only a few students pay attention when the teacher explains the material. Then, from the results of the students' daily test scores, it was also found that the low ability to understand mathematical concepts of grade IX students at SMP N 1, Gunuang Omeh District. The formulation of the problem in this study is how is the motivation of students to learn in mathematics subjects using the Student Teams Achievement Division (STAD) type cooperative learning model for grade IX at SMP N 1 Gunuang Omeh District for the 2023/2024 Academic Year and whether there is a significant positive influence using the Student Teams Achievement Division (STAD) type cooperative learning model on the ability to understand mathematics concepts of grade IX students at SMP N 1 Kecamatan Gunuang Omeh for the 2023/2024 Academic Year. This type of research is a quasi-experimental experiment with a Randomized Control Group Only Design research design. The population in this study is all grade IX students at SMP N 1, Gunuang Omeh District. Sampling was determined at random first by a normality test, a homogeneity test, and an average similarity test on population data. The sample in this study is class IX-2 as the experimental class and class IX-3 as the control class. The results of the analysis of the student mathematics learning motivation questionnaire data were obtained with a percentage of 72.28% with high motivation criteria and the test of students' ability to understand mathematical concepts was calculated using the t-test obtained tcount = 3.180 and and ttable = 1.672 because tcount > ttable means subtracting H0 and accepting H1 at the real level α=0.05, and by using SPSS26 Sig = 0.003 was obtained which means that sig ≤α with α=0.05.